Tsetse fly (Glossina pallidipes) midgut responses to Trypanosoma brucei challenge - Rosemary Bateta; Jingwen Wang; Yineng Wu; Brian L. Weiss; Wesley C. Warren; Grace A. Murilla; Serap Aksoy; Paul O. Mireji (Parasites & Vectors, 2017)
Abstract Background Tsetse flies (Glossina spp.) are the prominent vector of African trypanosome parasites (Trypanosoma spp.) in sub-Saharan Africa, and Glossina pallidipes is the most widely distributed species in Kenya. This species displays strong resistance to infection by parasites, which are typically eliminated in the midgut shortly after acquisition from the mammalian host. Although extensive molecular information on immunity for the related species Glossina morsitans morsitans exists, similar information is scarce for G. pallidipes. Methods To determine temporal transcriptional responses of G. pallidipes to Trypanosoma brucei brucei challenge, we conducted Illumina based RNA-seq on midgut organ and carcass from teneral females G. pallidipes at 24 and 48 h post-challenge (hpc) with T. b. brucei relative to their respective controls that received normal blood meals (without the parasite). We used a suite of bioinformatics tools to determine differentially expressed and enriched transcripts between and among tissues, and to identify expanded transcripts in G. pallidipes relative to their orthologs G. m. morsitans. Results Midgut transcripts induced at 24 hpc encoded proteins were associated with lipid remodelling, proteolysis, collagen metabolism, apoptosis, and cell growth. Midgut transcripts induced at 48 hpc encoded proteins linked to embryonic growth and development, serine endopeptidases and proteosomal degradation of the target protein, mRNA translation and neuronal development. Temporal expression of immune responsive transcripts at 48 relative to 24 hpc was pronounced, indicative of a gradual induction of host immune responses the following challenge. We also searched for G. m. morsitans orthologous groups that may have experienced expansions in the G. pallidipes genome. We identified ten expanded groups in G. pallidipes with putative immunity-related functions, which may play a role in the higher refractoriness exhibited by this species. Conclusions There appears to be a lack of strong immune responses elicited by gut epithelia of teneral adults. This in combination with a compromised peritrophic matrix at this stage during the initial phase of T. b. brucei challenge may facilitate the increased parasite infection establishment noted in teneral flies relative to older adults. Although teneral flies are more susceptible than older adults, the majority of tenerals are still able to eliminate parasite infections. Hence, robust responses elicited at a later time point, such as 72 hpc, may clear parasite infections from the majority of flies. The expanded G. m. morsitans orthologous groups in G. pallidipes may also be functionally associated with the enhanced refractoriness to trypanosome infections reported in G. pallidipes relative to G. m. morsitans.